The Effect of Asphalt Baths Wearing Coarse (AC–WC) on the Tide - Kemmala Dewi; Aris Krisdiyanto; Archi Rafferti Kriswandanu; Althea Serafim Kriswandaru (International Journal Labs, 2022)
The phenomenon of high tide that occurs in the coastal areas of Indonesia, especially on the island of Java which often results in floods or often called tidal floods. Tidal flooding is a flood event caused by the overflow of sea tides into coastal land. Often the overflow reaches on some roads located in coastal areas so that roads located in those coastal areas are damaged. Therefore, it is necessary to conduct research to investigate the effects caused by stagnant water on road pavement. The study used two standard methods of immersion in high tide and water in the laboratory. This study aims to determine the durability performance of the soaking mixture continuously (continuously) and periodically (intermittently). Soaking specimens (test objects) in a tide with a time variation of 12 hours; 24 hours; 48 hours; and 72 hours. While periodic soaking is carried out by soaking the specimen (test object) for 12 hours, then removed and allowed to stand for the next 12 hours for 3 days. Soaking the asphalt concrete wearing course (AC-WC) mixture either continuously or periodically in the tide has a greater influence compared to the use of laboratory water. This is indicated by the value of the Stability of the asphalt mixture in a bath with a tide smaller than the asphalt mixture soaked with laboratory standard water.